ISLAMIC EDUCATION MANAGEMENT STRATEGIES IN INSTILLING RELIGIOUS MODERATION VALUES AT DARUSSALAM GONTOR ISLAMIC BOARDING SCHOOL - Aulia, Nur Annisa; Awaluddin, Raisa Zuhra Salsabila Awaluddin Zuhra Salsabila; Nisa, Fitri Dwi Zahrotun; Ma’rifah, Rifa Tsamrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The issue of radicalism is often associated with religious education, including that conducted in boarding school. However, boarding school also play a strategic role in instilling religious moderation values that are relevant to building a harmonious and tolerant society. This study aims to analyze Islamic education management strategies in instilling religious moderation values at Darussalam Gontor Islamic Boarding School. The research uses a qualitative method with a field study approach. Data were collected through interviews, observations, and documentation, then analyzed descriptively-analytically. The theoretical framework used is the four indicators of religious moderation formulated by the Ministry of Religious Affairs of the Republic of Indonesia, namely tolerance, national commitment, anti-radicalism, and accommodation to local culture. The results showed that Darussalam Gontor Islamic Boarding School implemented an integrated curriculum-based education management strategy and habituation approach. First, the value of tolerance and national commitment is instilled through multiculturalism-based learning and strengthening of national insight. Second, the value of anti-radicalism is taught through balanced religious understanding (wasathiyah) and religious-humanist character building. Third, accommodation to local culture is realized through the integration of pesantren culture with local wisdom in learning activities and the daily life of students